2013
DOI: 10.1261/rna.040865.113
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of hepatitis C viral RNA abundance by precursor miR-122 molecules

Abstract: The hepatitis C viral RNA genome forms a complex with liver-specific microRNA (miR-122) at the extreme 5 ′ end of the viral RNA. This complex is essential to stabilize the viral RNA in infected cultured cells and in the liver of humans. The abundances of primary and precursor forms of miR-122, but not the abundance of mature miR-122, are regulated in a circadian rhythm in the liver of animals, suggesting a possible independent function of precursor molecules of miR-122 in regulating viral gene expression. Modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
(48 reference statements)
0
7
0
1
Order By: Relevance
“…S8A and S8B Fig shows that the abundance of pri-miR-122 is not affected by the depletion of Rab27a in uninfected and infected cells, suggesting that Rab27a modulates miR-122 abundance at a post-transcriptional step. Because precursor-miR-122 (pre-miR-122) can not be detected in cultured Huh7 cells, we determined the effect of Rab27a on the stability of a pre-miR-122 species that is resistant to the cleavage by Dicer [ 32 ]. Thus, the intracellular decay of a dicer-resistant pre-p3 (dNx12) that is functional in regulating mRNAs with miR-122 target sites [ 32 ] was examined ( S9A Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…S8A and S8B Fig shows that the abundance of pri-miR-122 is not affected by the depletion of Rab27a in uninfected and infected cells, suggesting that Rab27a modulates miR-122 abundance at a post-transcriptional step. Because precursor-miR-122 (pre-miR-122) can not be detected in cultured Huh7 cells, we determined the effect of Rab27a on the stability of a pre-miR-122 species that is resistant to the cleavage by Dicer [ 32 ]. Thus, the intracellular decay of a dicer-resistant pre-p3 (dNx12) that is functional in regulating mRNAs with miR-122 target sites [ 32 ] was examined ( S9A Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…These data may reflect the enhanced binding strength of miR-122 to S2 proposed by Mortimer and Doudna (32). This also has implications for explorations of the functions of miR-122, where Huh7.5 cells were supplemented with additional miR-122; and it is possible that supplementation may disproportionately measure effects of miR-122 binding to S1 (5,10,11,15,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Jopling et al (2005) showed that cellular HCV RNA decreased when miR-122 was inactivated. Since then, several published studies have revealed a requirement of miR-122 and/or its precursor molecule for HCV replication and stability (Jangra et al, 2010;Cox et al, 2013;Mortimer and Doudna, 2013) and successfully validated an anti-miR-122 therapy for suppression of viremia in chronically HCV infected primates (Lanford et al, 2010). Moreover, a study in which the serum from 102 HCV patients were compared to healthy controls identified a 23-fold increase of miR-122, indicating that it may be a useful biomarker to detect chronic HCV infections (van der Meer et al, 2013).…”
Section: Viral Hepatitismentioning
confidence: 99%